2021
DOI: 10.1080/14992027.2021.1957161
|View full text |Cite
|
Sign up to set email alerts
|

Is COVID-19 associated with self-reported audio-vestibular symptoms?

Abstract: Objective: To determine if a positive test for COVID-19 is associated with self-reported audio-vestibular symptoms. Design: Self-reported changes in hearing, tinnitus, hyperacusis, and dizziness/rotatory vertigo were assessed in hospitalised and non-hospitalised COVID-19 patients during and after the acute phase of the disease and compared to non-COVID controls. Study sample: There were 150 severe cases of COVID-19 requiring hospital admission and 150 mild cases that were managed at home. Controls were 267 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…However, it is important to recall that, for Type 2 and 3 symptoms, reports of auditory symptoms are similar in the COVID+ (confirmed cases) and COVID-0 groups. This is in agreement with a recent study ( 29 ) that reported similar proportions of auditory symptoms in COVID cases and non-COVID controls. Comparator groups are a fundamental design characteristic of high quality clinical trials which are lacking in the majority of studies in the systematic reviews summarized in the introduction.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is important to recall that, for Type 2 and 3 symptoms, reports of auditory symptoms are similar in the COVID+ (confirmed cases) and COVID-0 groups. This is in agreement with a recent study ( 29 ) that reported similar proportions of auditory symptoms in COVID cases and non-COVID controls. Comparator groups are a fundamental design characteristic of high quality clinical trials which are lacking in the majority of studies in the systematic reviews summarized in the introduction.…”
Section: Discussionsupporting
confidence: 93%
“…Although the scores indicating tinnitus annoyance, tinnitus effect on life, tinnitus effect on sleep, and HQ scores were higher after COVID-19, the differences before-after were not statistically significant. Additionally, as stated in the current literature, the relationship between COVID-19 and the onset of auditory symptoms or worsening of the preexisting ones might depend on the negative effects of the pandemic process and, therefore, should be established with care ( 12 , 43 ).…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, a higher incidence of these conditions in 2020 than in previous years, or a higher prevalence in COVID-19 patients, might be due to the ototoxicity of some medications, and could be expected ( 16 ). However, the issue is still debated ( 18 ).…”
Section: Introductionmentioning
confidence: 99%